2006
DOI: 10.4049/jimmunol.176.4.2470
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic CD8+ T Cells Directed against a Cryptic Epitope Derived from a Retroviral Alternative Reading Frame Confer Disease Protection

Abstract: Cytolytic CD8+ T cells (CTL) are key to the immune response that controls virus infections and mediates disease protection. The ability of CTL to induce apoptosis of infected cells and/or limit viral replication is determined by recognition of processed viral peptide epitopes on the surface of the target cell. An understudied source of MHC class I-presented peptides is the aptly named “cryptic epitopes,” defined by their nontraditional methods of generation, including derivation from alternative reading frames… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 40 publications
5
40
0
Order By: Relevance
“…In disease-resistant BALB/c mice, however, we have shown that CD8-deficient (chronic in vivo anti-CD8 MAb treated or CD8 KO) mice convert to disease susceptibility (27,45) and that WT BALB/c mice generate a strong antiviral CD8 ϩ T-cell response (63). Indeed, the BALB/c CD8 ϩ T effector cells are highly lytic, secrete IFN-␥, and are protective against LP-BM5 virus challenge in vivo, in terms of both inhibition of disease and the ultimate viral load, after their adoptive transfer into BALB/c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In disease-resistant BALB/c mice, however, we have shown that CD8-deficient (chronic in vivo anti-CD8 MAb treated or CD8 KO) mice convert to disease susceptibility (27,45) and that WT BALB/c mice generate a strong antiviral CD8 ϩ T-cell response (63). Indeed, the BALB/c CD8 ϩ T effector cells are highly lytic, secrete IFN-␥, and are protective against LP-BM5 virus challenge in vivo, in terms of both inhibition of disease and the ultimate viral load, after their adoptive transfer into BALB/c.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the BALB/c CD8 ϩ T effector cells are highly lytic, secrete IFN-␥, and are protective against LP-BM5 virus challenge in vivo, in terms of both inhibition of disease and the ultimate viral load, after their adoptive transfer into BALB/c. CD8 KO recipients (27,44). Of note, both the polyclonal and clonal CD8 ϩ T-cell populations that were protective were specific for a unique K d -presented immunodominant epitope, SYNTGRFPPL, which derives from a previously unrecognized alternative (ϩ1 nucleotide) gag translational open reading frame of the LP-BM5 retrovirus (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Such epitopes positioned in an area of overlapping reading frames might make excellent candidates for conserved targets that the virus cannot vary to escape from immune detection. Thus, despite their presumably low abundance, ARF epitopes can be expressed at functional levels in vivo at the priming stage and at the target level without the use of overexpression systems (9), and can provide in vivo targets for protective immune responses (29,48).…”
Section: Discussionmentioning
confidence: 99%
“…1) (9). By adoptive transfer studies using disease-susceptible CD8-deficient BALB/c recipient mice, we have reported recently a physiologically relevant role for this ARF-encoded ORF2 epitope by demonstrating CTL-mediated full protection against LP-BM5-induced disease in vivo (29).…”
Section: Strongly Lytic Cd8mentioning
confidence: 99%
See 1 more Smart Citation